Blindeninstituut Bandung: Sekolah Pertama untuk Penyandang Disabilitas di Hindia-Belanda - Rifai Shodiq Fathoni (Balai Pelestarian Kebudayaan Wilayah X, 2023)
This study aims to explore the earliest education for people with disabilities during the colonial period, specifically focusing on the blind at Blindeninstituut Bandung. The primary issue addressed in this research is the reason behind the attempt to educate the blind during the colonial period. The research employs historical methods, including heuristics, source criticism, interpretation, and historiography. The emergence of Blindeninstituut Bandung serves as a response to the problem of blindness in Java, which resulted in many visually impaired individuals of working age having to depend on begging to sustain their lives. On the other hand, the colonial government, through its policies, failed to allocate sufficient resources for people with disabilities. Through the social innovations introduced by Blindeninstituut, blind individuals are educated and trained to become independent individuals and secure a future for themselves.` The presence of Blindeninstituut, which is funded by private donors, such as the masonic lodge, serves as evidence that societal awareness of the rights of people with disabilities had emerged during the colonial period.